2005
DOI: 10.1111/j.1600-0668.2005.00354.x
|View full text |Cite
|
Sign up to set email alerts
|

Endotoxin exposure in asthmatic children and matched healthy controls: results of IPEADAM study

Abstract: This study has demonstrated that the home environments of English children (4-17) with asthma and without the disease do not differ greatly. With the exception of endotoxin, the parameters examined in this study, including house dust mite allergens, nitrogen dioxide, ETS and damp are unlikely to be related to the development of asthma. Avoidance of these pollutants may not be beneficial in preventing asthma in this age group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 42 publications
2
42
1
Order By: Relevance
“…In a cohort of 1,884 German newborns, a two-fold increased risk of wheezing during the first 6 months of life was found in children exposed to high endotoxin concentrations (OR 2.37, 95% CI 1.40-4.03) [78]. Such associations have been confirmed in other longitudinal studies [79,80,84], as well as in case-control or crosssectional studies [81][82][83]. Moreover, exposure to endotoxins has been linked to asthma severity and morbidity [86,87].…”
Section: Endotoxinssupporting
confidence: 69%
See 2 more Smart Citations
“…In a cohort of 1,884 German newborns, a two-fold increased risk of wheezing during the first 6 months of life was found in children exposed to high endotoxin concentrations (OR 2.37, 95% CI 1.40-4.03) [78]. Such associations have been confirmed in other longitudinal studies [79,80,84], as well as in case-control or crosssectional studies [81][82][83]. Moreover, exposure to endotoxins has been linked to asthma severity and morbidity [86,87].…”
Section: Endotoxinssupporting
confidence: 69%
“…Findings from epidemiological studies are less consistent [74]. Whereas some reports suggest a protective effect of endotoxins on the development of allergies [57,[75][76][77], others found that the exposure to endotoxins constitutes a risk factor for respiratory symptoms [78][79][80][81][82][83][84], which might depend on the amount of exposure [85].…”
Section: Endotoxinsmentioning
confidence: 80%
See 1 more Smart Citation
“…For example, one birth cohort found that early endotoxin exposure was associated with an increased risk of atopy at the age of 2 years [32], whereas two similar birth cohort studies found a protective effect on atopy in 2-year-olds [28] and asthma symptoms in 4-year-olds [30]. Endotoxin exposure has also been shown to be a risk factor for asthma as demonstrated in inner city urban environments [33,34].…”
Section: Noninfectious Microbesmentioning
confidence: 93%
“…It is known that endotoxins increase the risk for asthma development (Tavernier et al, 2005) and occupational respiratory symptoms (Douwes et al, 2003). In the toxicological studies, endotoxin has been linked to increased inflammatory responses (e.g.…”
Section: Introductionmentioning
confidence: 99%